2018
DOI: 10.4103/ija.ija_1_18
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the pressor responses to laryngoscopy and endotracheal intubation with intravenous dexmedetomidine versus magnesium sulphate under bispectral index-controlled anaesthesia: A placebo-controlled prospective randomised trial

Abstract: Background and Aims:Laryngoscopy and intubation cause sympathetic stimulation and arousal reactions. We evaluated the role of dexmedetomidine and magnesium sulphate on pressor responses to laryngoscopy and intubation as compared to placebo, when depth of anaesthesia was maintained at a constant bispectral index (BIS) range 40-50 (±5).Methods:One hundred and twenty patients were randomised to receive either dexmedetomidine 1 μg/kg (Group DS), magnesium sulphate 30 mg/kg diluted in 100 ml saline (Group MS) or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
2
21
2
Order By: Relevance
“…Various studies have investigated the effects of intravenous dexmedetomidine on the hemodynamic response to laryngoscopy and intubation [ 11 15 , 23 26 ]. While doses of 1–2 µg/kg have been found to be effective in attenuating this hemodynamic response, they are associated with significant side effects, such as bradycardia, hypotension, or respiratory depression [ 24 , 25 ]. Lawrence and De Lange [ 24 ], found that a single dose of 2 µg/kg dexmedetomidine caused a higher incidence of bradycardia and hypotension compared with the placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the effects of intravenous dexmedetomidine on the hemodynamic response to laryngoscopy and intubation [ 11 15 , 23 26 ]. While doses of 1–2 µg/kg have been found to be effective in attenuating this hemodynamic response, they are associated with significant side effects, such as bradycardia, hypotension, or respiratory depression [ 24 , 25 ]. Lawrence and De Lange [ 24 ], found that a single dose of 2 µg/kg dexmedetomidine caused a higher incidence of bradycardia and hypotension compared with the placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The consequences of laryngoscopy and intubation may precipitate ischaemia, arrhythmias, cerebrovascular stroke, pulmonary oedema, increase in intracranial pressure in the vulnerable group. [ 2 ] Till date, numerous drugs and various routes have been tried to attenuate this stress response such as opioids, vasodilators, beta-blockers, calcium channel blockers, intravenous lignocaine, topical sprays, volatile agents, α2 agonists but none of the agents proved to be ideal. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Various methods to attenuate the sympathetic response to laryngoscopy and achieve smoother manipulation of airway have been evaluated like topical anaesthesia of pharynx, superior laryngeal nerve block, intravenous lidocaine, beta blockers, opioids, calcium channel blockers, benzodiazepines, barbiturates, propofol, pregabalin, magnesium sulphate, nitroglycerin (intranasal and intravenous) and alpha2 adrenoceptor agonists like clonidine and dexmedetomidine (intravenous and intranasal). [ 4 5 6 ] However, the use of these agents is associated with the respective adverse effects like respiratory depression, hypotension, tachycardia, bradycardia, rebound hypertension or allergic reactions; hence, the quest for a better agent is always on.…”
Section: Introductionmentioning
confidence: 99%